Alpha-Tocopherol Levels in Patients With Dentigerous Cysts: A Cross-Sectional Study - Ubayathulla, Nausathkhan; M.R, Muthusekar; Ramani, Pratibha; S, Dharini; Kizhakkoottu, Suvarna; Ramalingam, Karthikeyan (Curēus (Palo Alto, CA), 2024)
Background Dentigerous cysts (DC) form due to fluid accumulation between the crown of the tooth and the reduced enamel epithelium. Due to the diverse clinical characteristics, such as ambiguity concerning their biological origins and the significance of timely diagnosis and detection of these lesions, researchers are presently motivated to undertake further investigations. The aim of the present study was to assess the amount of serum alpha-tocopherol in patients with DC and compare it with that of normal, healthy individuals. Methods A total sample size of n=34 was included in the current study. Group A, designated as the control group, comprised 17 randomly selected healthy subjects, while Group B, the DC diagnostic group, consisted of 17 patients. Blood samples were collected, and the concentration of vitamin E or alpha-tocopherol was evaluated and expressed in mg/mL. Results Compared to the mean vitamin E level in healthy controls (12.08 ± 1.92 mg/mL), patients with DC showed a statistically significant (p<0.0001) reduction in mean vitamin E levels (5.29 ± 1.01 mg/mL). Conclusion Patients with DC have lower levels of vitamin E than healthy individuals. The reduced concentration of vitamin E can have a role in the extension of cystic volume and thus have an impact on the aggressiveness of pathologic lesions. The therapeutic benefits of vitamin E supplementation in reducing the aggressiveness of DC should be evaluated in future research.